Aeolian Remobilisation of Volcanic Ash: Outcomes of a Workshop in the Argentinian Patagonia - Jarvis, Paul A.; Bonadonna, Costanza; Dominguez, Lucia; Forte, Pablo; Frischknecht, Corine; Bran, Donaldo; Aguilar, Rigoberto; Beckett, Frances; Elissondo, Manuela; Gillies, John; Kueppers, Ulrich; Merrison, Jonathan; et al. (Frontiers in Earth Science, 2020)
During explosive volcanic eruptions, large quantities of tephra can be dispersed and deposited over wide areas. Following deposition, subsequent aeolian remobilisation of ash can potentially exacerbate primary impacts on timescales of months to millennia. Recent ash remobilisation events (e.g., following eruptions of Cordón Caulle 2011, Chile, and Eyjafjallajökull 2010, Iceland) have highlighted this to be a recurring phenomenon with consequences for human health, economic sectors, and critical infrastructure. Consequently, scientists from observatories and Volcanic Ash Advisory Centres (VAACs), as well as researchers from fields including volcanology, aeolian processes and soil sciences, convened at the San Carlos de Bariloche headquarters of the Argentinian National Institute of Agricultural Technology to discuss the ‘state of the art’ for sampling remobilised deposits as well as monitoring, modelling and understanding ash remobilisation. In this article, we identify practices for field characterisation of deposits and active processes, including mapping, particle characterisation and sediment traps. Furthermore, since forecast models currently rely on poorly-constrained dust emission schemes, we call for laboratory and field measurements to better parameterise the flux of volcanic ash as a function of friction velocity. Whilst source area location and extent are currently the primary inputs for dispersion models, once emission schemes become more sophisticated and better constrained, other parameters will also become important (e.g., source material volume and properties, effective precipitation, type and distribution of vegetation cover, friction velocity). Thus, there is a need for systematic monitoring of wind-driven ash resuspension, including the development of a regularly-updated spatial database of resuspension source areas.